Medizinischer Untersuch in Bad Kreuzen eines Mannes
soziale Fragen;Gesundheit;ärztlicher Beruf;Arzt/Ärztin soziale Fragen;Gesundheit;Medizin;medizinische Untersuchung soziale Fragen;Wanderungsbewegungen;Asylpolitik;Flüchtlingsbetreuung